Mycorrhizal biofertilizer: advantages and hindrances in its application - Somdatta Ghosh; Som Subhra Dutta; Suvashree Bhaumik; Kunwar Hansda; Debashis Kuila (Lilloa, 2025)
Global climate change, rising population growth, and the overuse of agrochemicals have led to various problems, including soil degradation, a decline in food production, and environmental issues affecting the agricultural sector. To overcome these challenges, biofertilizers (particularly, those of mycorrhizal origin) have emerged as a sustainable and eco-friendly alternative. Arbuscular mycorrhiza (AM) is an association between plant roots and fungi from the subphylum Glomeromycotina, found in approximately 72% of land plants, and is one of the most common and ancient types of symbiosis on Earth. AM fungi provide with numerous benefits in exchange for plant photoassimilates. Although AM fungi may represent a viable biofertilizer option, their use is significantly limited due to various issues, ranging from their production to field application. This review sheds light on the potential of AM fungi as biofertilizers, analyzing their diverse benefits while also addressing the limitations associated with their production and application for enhancing agricultural productivity.